2016
DOI: 10.3390/s16050718
|View full text |Cite
|
Sign up to set email alerts
|

A Tactile Sensor Using Piezoresistive Beams for Detection of the Coefficient of Static Friction

Abstract: This paper reports on a tactile sensor using piezoresistive beams for detection of the coefficient of static friction merely by pressing the sensor against an object. The sensor chip is composed of three pairs of piezoresistive beams arranged in parallel and embedded in an elastomer; this sensor is able to measure the vertical and lateral strains of the elastomer. The coefficient of static friction is estimated from the ratio of the fractional resistance changes corresponding to the sensing elements of vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The working mechanism of our pressure sensor is schematically illustrated in Figure a. When the sensor is being pressed, the two layers of CNTs electrodes will deform and sink into the SU‐8 holes, while the SU‐8 insulation layer remains unchanged, because PDMS can be deformed much easier than SU‐8 (Young's modulus of SU‐8: 2 GPa, Young's modulus of PDMS: 600 kPa). Under a critical pressure ( P 0 ), which is also the sensing threshold, these two electrodes are just brought into contact, allowing a current to flow between them.…”
Section: Resultsmentioning
confidence: 99%
“…The working mechanism of our pressure sensor is schematically illustrated in Figure a. When the sensor is being pressed, the two layers of CNTs electrodes will deform and sink into the SU‐8 holes, while the SU‐8 insulation layer remains unchanged, because PDMS can be deformed much easier than SU‐8 (Young's modulus of SU‐8: 2 GPa, Young's modulus of PDMS: 600 kPa). Under a critical pressure ( P 0 ), which is also the sensing threshold, these two electrodes are just brought into contact, allowing a current to flow between them.…”
Section: Resultsmentioning
confidence: 99%
“…Okatani et al [102] describe a tactile sensor, composed of three pairs of parallel piezoresistive beams embedded in an elastomer (Fig. 15), which is able to measure normal and shear strains of the elastomer that are caused by applying a normal force.…”
Section: Friction Estimation On Contactmentioning
confidence: 99%
“…The above sensors that propose measuring stress/strain in order to estimate μs at initial contact with an object, were able to show that the stress and strain distributions were dependent on μs; however, most did not attempt to define a relationship between the measured quantities and μs [98,99,102]. A relationship between strain and μs was found in [101]; however, the range of μs for which the sensor was operational was severely limited (μs < 0.5).…”
Section: Friction Estimation On Contactmentioning
confidence: 99%
“…Shear force can be measured via a bridge circuit, as shown in Figure 11 b. The later work of their group demonstrated that the sensor could also be used to measure the coefficient of static friction [ 129 ].…”
Section: Transduction Mechanismsmentioning
confidence: 99%